Leadership role of coaches in improving teachers’ instructional practices - Shafee, Salwati; Ghavifekr, Simin; Abdullah, Zuraidah (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2019)
Changing instructional practices is not an easy job. Therefore, teachers need help and support in order to create changes in their practices. In some countries like Malaysia, the support is offered through coaching. Effective coaching takes place if teachers and coaches play their effective leadership roles and equip themselves with various attributes of coaching. Subsequently, this allows instructional changes to take place. A traditional idea of leadership focus on an individual managing a hierarchical system. Therefore, it poses a significant barrier for teachers to work together and does not provide teachers with autonomy as a leader. In the practice of coaching however, teachers play the different roles of leadership. Hence, this study looks at the perception of teachers and coaches on the implementation of coaching in Malaysian schools. Moreover, it looks at a form of instructional support given to teachers in helping them to improve their classroom practices which eventually leads to increased students’ learning outcome. This article specifically discusses the application of five attributes of coaching namely collaboration, support, feedback, reflect and trust. The study also looks at the leadership role of the coaches in coaching teachers to create instructional improvements. Data of this quantitative study were gathered through a set of questionnaires which was administered to 470 teachers and coaches in primary and secondary school in Selangor and Sabah. Analysis of findings were based on descriptive analysis using SPSS as well as inferential analysis using Smart PLS. The findings of the study provide and insight on the role of coaching attributes and coaching leadership in helping teachers and coaches to create changes and improvements in classroom practices which leads to increased learning outcomes. It also illustrates the significant relationship between coaching attributes and the role of leadership in the implementation of coaching in Malaysian schools. © 2019, University of Malaya. All rights reserved.